Epiphytic Diatoms on Nuphar lutea L. in Three Shallow Turkish Lakes - Soylu, E.N.; MaraÅŸlioÇ§lu, F.; Gönölol, A. (Taylor & Francis Inc, 2005)
Epiphytic algae growing on the submersed macrophyte Nuphar lutea L. were surveyed in three lakes in June 2000 and May 2001. All total, forty species of Bacillariophyta were identified, and the species composition of this algal flora differed among the three lakes. Navicula cryptocephnla, Navicula veneta, Cymbella affinis and Licmophora gracilis var. angiica were common in Ladik Lake. Cocconeis pediculus and Cocconeis disculus were major components of the epiphytic algae in Lake Tatlı and Lake Gıcı; and, Navicula salinarum and Navicula halophila, indicators of high salinity, were also found abundantly in these lakes. © 2005, Copyright Taylor & Francis Group, LLC.